HYPOKALEMIA-INDUCED NEPHROGENIC DIABETES INSIPIDUS IN REFEEDING SYNDROME - Wong, Wei Ton; Chong, Jia Chuan; Shah, Raja Nurul Azafirah Raja Amir (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Nephrogenic diabetes insipidus is a rare disorder in which the body produces excessive amounts of urine. It can be caused by a genetic mutation or acquired factors such as certain medications (lithium, amphotericin-B), electrolyte imbalance (hypokalemia, hypercalcemia), chronic kidney disease or obstructive uropathy. In this case report, we describe a case of refeeding syndrome followed by hypokalemia-induced nephrogenic diabetes insipidus. CASE A cachectic 37-year-old male with BMI of 15.0 kg/m² with underlying mild intellectual disability and history of pulmonary tuberculosis (TB) who had completed his TB treatment presented at the emergency department with 2 weeks history of vomiting and 3 weeks history of bilateral lower limb weakness, loss of appetite and weight loss. Vital signs were stable. Systemic examination revealed bilateral lower limb weakness with power of 4/5. Laboratory data were significant for hypokalemia (1.8 mmol/L), hypophosphatemia (0.48 mmol/L) and hypocalcemia (1.6 mmol/L). The patient was admitted for electrolyte correction. At the ward, patient was noted to be producing excessive amounts of urine ranging from 4 to 10 L/day. Water deprivation test was performed. It showed failure to increase urine osmolality with water deprivation and lack of response to desmopressin suggestive of nephrogenic diabetes insipidus. Spot urine potassium was low at 9.8 mmol/L. With multiple corrections of electrolytes, hypokalemia, hypophosphatemia and hypocalcemia gradually resolved. The patient was started on a low-calorie, high-protein diet for the consideration of refeeding syndrome. Following correction of electrolytes with potassium reaching a stable level of 4 mmol/L, on the 17th day of admission, the daily urine output was restored to a normal volume of approximately 2 L/day. After three days, he was discharged. CONCLUSION Patients with polyuria and hypokalemia should be evaluated for nephrogenic diabetes insipidus. Hypokalemia-induced nephrogenic diabetes insipidus can be reversed by correcting hypokalemia.